Seismic performance analysis of blast furnace shell structure - W. Zhang (Croatian Metallurgical Society, 2022)
In this paper, the finite element software ANSYS is used to establish a three-dimensional space model of the blast furnace shell, and the static analysis of the space steel structure system of the blast furnace is carried out. The seismic response of the outer shell system of the blast furnace is analyzed by response spectrum method and linear time history analysis method, so as to explore the seismic response of the blast furnace shell.